Effectiveness and safety of anti-BCMA chimeric antigen receptor T-cell treatment in relapsed/refractory multiple myeloma: a comprehensive review and meta-analysis of prospective clinical trials - Hu, Dingyuan; Chen, Liming; Yan, Diqin; Dong, Wenliang; Chen, Min; Niu, Suping; Wang, Simin; Zhang, Jiaojiao; Nie, Xiaoyan; Fang, Yi (Frontiers in Pharmacology, 2023)
Background: Chimeric antigen receptor T cells treatment targeting B cell maturation antigen (BCMA) is an emerging treatment option for relapsed/refractory multiple myeloma (RRMM) and has demonstrated outstanding outcomes in clinical studies. Objective: The aim of this comprehensive review and meta-analysis was to summarize the effectiveness and safety of anti-BCMA CAR-T treatment for patients with relapsed/refractory multiple myeloma (RRMM). Our research identifies variables influencing outcome measures to provide additional evidence for CAR-T product updates, clinical trial design, and clinical treatment guidance. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard was followed for conducting this comprehensive review and meta-analysis, which was submitted to PROSPERO (CRD42023390037). From the inception of the study until September 10th, 2022, PubMed, Web of Science, EMBASE, the Cochrane Library, CNKI, and WanFang databases were searched for eligible studies. Stata software (version 16.0) was used to assess effectiveness and safety outcomes. Results: Out of 875 papers, we found 21 relevant trials with 761 patients diagnosed as RRMM and were given anti-BCMA CAR-T treatment. The overall response rate (ORR) for the entire sample was 87% (95% CI: 80 ~ 93%) complete response rate (CRR) was 44% (95% CI: 34 ~ 54%). The minimal residual disease (MRD) negativity rate within responders was 78% (95% CI: 65 ~ 89%). The combined incidence of cytokine release syndrome was 82% (95% CI: 72 ~ 91%) and neurotoxicity was 10% (95% CI: 5-17%). The median progression-free survival (PFS) was 8.77 months (95% CI: 7.48-10.06), the median overall survival (OS) was 18.87 months (95% CI: 17.20-20.54) and the median duration of response (DOR) was 10.32 months (95% CI: 9.34-11.31). Conclusions: According to this meta-analysis, RRMM patients who received anti-BCMA CAR-T treatment have demonstrated both effectiveness and safety. Subgroup analysis confirmed the anticipated inter-study heterogeneity and pinpointed potential factors contributing to safety and efficacy, which may help with the development of CAR-T cell studies and lead to optimized BCMA CAR-T-cell products.